(untitled)
The results of initial electric field activity and precipitation process in nine thunder storms at Poona are presented and compared with the findings of previous workers. The storms are classified as Type ’A’ and Type ’B’storms, In Type ’A’storms the surface field first increases when the size of the precipitation particles reach a definite size showing that the charge separat:on process in clouds is related directly to the precipitation process, The first appearance 0! precipitation beneath. the cloud appears, usually about twenty minutes after the first increase of electric field occurs, The positive electric field then decreases, becomes zero, and reversed to the negative direction as soon as the precipitation starts. In Type ’B’ storms, the field reversal suddenly takes place before the onset of rain at the ground. There is a distinct time lag between the field reversal and onset of rainfall at the ground during thunderstorm. This enables us to get an approximate idea of the distance of fall of raindrops, assuming the terminal velocity for the average size of rain drops for a particular rate of rainfall at onset, The approximate temperature of the origin of raindrops can then be calculated with some limitations, Evidence is given in certain isolated thunderstorm cell growth that the development of electric field is associated with the initial radar (10 cm